HIDUPKU DI TANGAN SANG PENJUNAN: Kajian Hermeneutik Kritik Historis Terhadap Yeremia 18:1-17 Dan Maknanya Bagi Pemuda Jemaat Gmim Betel Wilayah Manado Teling Tingkulu - Tumbel, Tesalonika Hane; Masambe, Helen Gratia (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2021)
Jeremiah 18:1-17 talks about God who prepared Jeremiah to be sent to His people, Israel. Jeremiah asked to go to see how the potter work as an illustration of God’s supervision in the midst of the lives of His people. This text was studied using a Historical Criticism Hermeneutic which aims to explore the meaning of the text and uses qualitative research methods to determine the meaning of the text in relation to young people’ life. This research shows that the lives of young people have not yet fully submitted themselves to being shaped by God.